Pengajaran Bahasa Arab di Pondok Pesantren Salafiyah Kalimantan Timur - Abdullah, Rais (IAIN Samarinda, 2014)
The Arabic Language, as the language of Islam religion, and also the language of the Holy Quran, obtaining a privileged position in the heart of Indonesians, especially Muslims. Due to its privileged position, the Arabic language was able to survive from its extinction since its appearance in Indonesia until now. Unfortunately, the privileged position of Arabic language is not directly proportional to its fate in various educational institutions in Indonesia, especially in East Kalimantan. The Arabic language teaching in those institutions faces very complex problems especially the lack of an integrated curriculum that can be relied upon to fulfill the needs of teaching Arabic language to non- Arabs with a better method. The current curriculum is the curriculum that does not have comprehensive programs and is not accompanied with modern teaching methods. While at the Teaching and Learning Activities stage, teaching the Arabic language is not supported by professional and competent teachers. This study aims to analyze and evaluate approaches used in teaching Arabic at some boarding school in East Kalimantan viewed from the perspective of the curriculum and methods of teaching Arabic to non- Arabs.